Proceedings of the 29th Annual ACM Symposium on Applied Computing 2014
DOI: 10.1145/2554850.2554953
|View full text |Cite
|
Sign up to set email alerts
|

Bespoke video games to provide early response markers to identify the optimal strategies for maximizing rehabilitation

Abstract: Stroke commonly leads to partial or complete paralysis of one side of the body and there is limited availability of therapists to provide rehabilitation. It is a priority therefore to identify the most effective rehabilitation strategies and/or pharmacotherapies. Motor learning, the essential process underpinning rehabilitation, can be assessed more quickly and robustly than outcomes from rehabilitation. In this paper we describe a proof of concept system that utilises a bespoke video game to measure the criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…We chose therefore to investigate intermanual transfer to the left hand of the motor skills acquired while young and older adults learn to perform with their right hand a novel myoelectric-controlled interface task comprising two sequentially linked action components (Graziadio et al, 2014;Nazarpour, Barnard, & Jackson, 2012;Radhakrishnan, Baker, & Jackson, 2008). The first component requires feedforward motor learning, when predominantly unilateral activation of motor networks in the young adults and bilateral activation in the elderly has been demonstrated across a range of visuomotor tasks involving hand muscles and using a range of experimental techniques (Mattay et al, 2002;Sailer et al, 2000;Seidler, Noll, & Thiers, 2004;Ward & Frackowiak, 2003;Wu & Hallett, 2005;Yordanova et al, 2004); the second component requires feedback learning, when bilateral activation of motor networks in both age groups has been consistently demonstrated (Grafton, Schmitt, Van Horn, & Diedrichsen, 2008;Noble, Eng, Kokotilo, & Boyd, 2011;Ullsperger, Harsay, Wessel, & Ridderinkhof, 2010).…”
mentioning
confidence: 99%
“…We chose therefore to investigate intermanual transfer to the left hand of the motor skills acquired while young and older adults learn to perform with their right hand a novel myoelectric-controlled interface task comprising two sequentially linked action components (Graziadio et al, 2014;Nazarpour, Barnard, & Jackson, 2012;Radhakrishnan, Baker, & Jackson, 2008). The first component requires feedforward motor learning, when predominantly unilateral activation of motor networks in the young adults and bilateral activation in the elderly has been demonstrated across a range of visuomotor tasks involving hand muscles and using a range of experimental techniques (Mattay et al, 2002;Sailer et al, 2000;Seidler, Noll, & Thiers, 2004;Ward & Frackowiak, 2003;Wu & Hallett, 2005;Yordanova et al, 2004); the second component requires feedback learning, when bilateral activation of motor networks in both age groups has been consistently demonstrated (Grafton, Schmitt, Van Horn, & Diedrichsen, 2008;Noble, Eng, Kokotilo, & Boyd, 2011;Ullsperger, Harsay, Wessel, & Ridderinkhof, 2010).…”
mentioning
confidence: 99%
“…While much medical research is based on quantitative biometric data that can be measured or observed in the patient, it is often the case that the available methods for collecting data are more qualitative. In such cases, medical markers must be identified within the soft data that is accrued [4], [2]. The analysis of soft data requires techniques for understanding qualitative results, which are by definition open to some interpretation [6].…”
Section: Background and Related Work 21 Soft Data Analysismentioning
confidence: 99%
“…HCI research has started to address the design, implementation and evaluation of bespoke games, e.g. for physical therapy [13], rehabilitation [15], enjoyment for children with motor disabilities [19]. Bespoke games for this audience often need to be simple [27], require simplified control schemes or accessibility features [19], and need to adapt to player performance that can vary over the course of a day [3].…”
Section: Related Workmentioning
confidence: 99%